Feasibility of an inpatient exercise intervention for children undergoing hematopoietic stem cell transplant. (31st October 2015) - Bogg, Tina Fung Ting; Broderick, Carolyn; Shaw, Peter; Cohn, Richard; Naumann, Fiona Leigh
Abstract: With improving survival rates following HSCT in children, QOL and management of short‐ and long‐term effects need to be considered. Exercise may help mitigate fatigue and declines in fitness and strength. The aims of this study were to assess the feasibility of an inpatient exercise intervention for children undergoing HSCT and observe the changes in physical and psychological health. Fourteen patients were recruited, mean age 10 yr. A 6MWT, isometric upper and lower body strength, balance, fatigue, and QOL were assessed prior to Tx and six wk post‐Tx. A supervised exercise program was offered five days per week during the inpatient period and feasibility assessed through uptake rate. The study had 100% program completion and 60% uptake rate of exercise sessions. The mean (±s.d.) weekly activity was 117.5 (±79.3) minutes. Younger children performed significantly more minutes of exercise than adolescents. At reassessment, strength and fatigue were stabilized while aerobic fitness and balance decreased. QOL revealed a non‐statistical trend towards improvement. No exercise‐related adverse events were reported. A supervised inpatient exercise program is safe and feasible, with potential physiological and psychosocial benefits.